Human behaviour on tree vandalism / Muhammad Abid Luqman and Helmi Hamzah - Luqman, Muhammad Abid; Hamzah, Helmi (2024)
Urban trees provide a variety of social and ecological purposes and are an important component of urban sustainability. However, deliberate vandalism is a risk for urban trees. This may result in high rates of tree death and poor tree development. This problem is very challenging to conflict because urban tree managers are unable to recognize a tree's qualities. It might make vandalism more likely. In order to better understand the factors that influence tree vandalism in the Seri Iskandar area, this study analyses data from site samples of site public reports of tree vandalism. A community-maintained database that complied with local laws was utilized to determine the most commonly vandalized tree species. A quantitative study was performed on the data, and societal tendencies related to vandalism of urban trees were looked at.a systematic research have also been made in order to refine the database that have been collect. The location, values, and condition of the tree were shown to be the three factors that enhanced the chance of vandalism, these factors also had a significant positive link with urban tree vandalism. In order to guarantee the survival of trees in urban environments, this study aims to provide guidance to urban tree managers and tree carers regarding how to enhance tree planting programmed.